The Use of Authentic Materials Toward Students' Critical Thinking Skill - Iis Sulyaningsih (Jurnal Bahasa Inggris Terapan, 2021)
This study was conducted to investigate the use of ‘authentic materials’ in reading to promote students’ critical thinking. Critical thinking ability becomes important since it includes analyzing problems, making decisions, and solving problems that will affect daily life attitudes. A qualitative method was applied in this research: the data were analyzed, referring to critical reading questions and text analysis framework by Robert McGregor (2001). The results show that students’ thinking skill level is analyzed by referring to the stages of Critical Thinking Rubric and Bloom’s Taxonomy. This study discovered that authentic materials can be used as effective teaching materials to promote students’ critical thinking abilities. However, the students’ thinking ability was in the comprehension stage. This implies that the use of authentic materials should also be supported by other aspects such as; suitable chosen texts and appropriate teaching methods.